2019
DOI: 10.1002/hyp.13630
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evapotranspiration rates for rainfed corn versus perennial bioenergy crops in a mesic landscape

Abstract: Perennial cellulosic crops are promoted for their potential contributions to a sustainable energy future. However, a large-scale perennial bioenergy production requires extensive land use changes through diversion of croplands or conversion of uncultivated lands, with potential implications for local and regional hydrology. To assess the impact of such land use conversions on ecosystem water use, we converted three 22 year-old Conservation Reserve Program (CRP) grasslands and three 50+ year-old conventionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Each tower was equipped with an infrared gas analyzer (LI-7500, LI-COR Biosciences, Lincoln, NE, USA) and a 3D sonic anemometer (CSAT3, Campbell Scientific Inc., Logan, UT, USA), with sensor heights 1.5–2.0 m above canopy heights [ 67 ]. Fluxes were processed following Ameriflux guidelines, with 30-min average fluxes (i.e., net ecosystem production, NEP) computed with EdiRe [ 68 ] and then gap filled and partitioned into gross primary production (GPP) and ecosystem respiration using REddyProc [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each tower was equipped with an infrared gas analyzer (LI-7500, LI-COR Biosciences, Lincoln, NE, USA) and a 3D sonic anemometer (CSAT3, Campbell Scientific Inc., Logan, UT, USA), with sensor heights 1.5–2.0 m above canopy heights [ 67 ]. Fluxes were processed following Ameriflux guidelines, with 30-min average fluxes (i.e., net ecosystem production, NEP) computed with EdiRe [ 68 ] and then gap filled and partitioned into gross primary production (GPP) and ecosystem respiration using REddyProc [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…(2015) and Abraha et al. (2020) found that this was not necessarily the case at a southern Michigan site, where ET from the perennial grasses was comparable to maize in both wet and dry years based on measurements of soil water uptake and eddy covariance, respectively. They proposed that this discrepancy could be attributed to development of water‐limited conditions during most years in the well‐drained sandy loam soils of the Michigan site.…”
Section: Introductionmentioning
confidence: 97%
“…Field studies that have compared ET in annual crops to that of perennial biofuel crops are fairly limited, and the results have been mixed. For well-drained soils, some studies have found that both crop types have similar growing-season ET rates (Abraha et al, 2015;Abraha et al, 2020;Hamilton et al, 2015;Parish et al, 2019), while perennials have higher growing-season ET rates than annual crops in soils with high water tables (Hickman et al, 2010;Zeri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Field studies that have compared ET in annual crops to that of perennial biofuel crops are fairly limited, and the results have been mixed. For well‐drained soils, some studies have found that both crop types have similar growing‐season ET rates (Abraha et al, 2015; Abraha et al, 2020; Hamilton et al, 2015; Parish et al, 2019), while perennials have higher growing‐season ET rates than annual crops in soils with high water tables (Hickman et al, 2010; Zeri et al, 2013). Similarly, mixed results come from modelling studies, as some show no difference in growing‐season ET rates (Song et al, 2016), while others show higher growing‐season ET rates for perennials than for annuals (Le et al, 2011; Schilling et al, 2008; VanLoocke et al, 2012; Zhuang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%